2017
DOI: 10.1155/2017/8130140
|View full text |Cite
|
Sign up to set email alerts
|

LSVT-BIG Improves UPDRS III Scores at 4 Weeks in Parkinson’s Disease Patients with Wearing Off: A Prospective, Open-Label Study

Abstract: The efficacy of LSVT-BIG for advanced Parkinson's disease (PD) patients with wearing off remains to be determined. Therefore, we evaluated whether LSVT-BIG improves motor disability in eight PD patients with wearing off. Unified Parkinson's Disease Rating Scale (UPDRS) scores, daily off time, and mobility assessments were evaluated during the “on” time before and after the LSVT-BIG course. LSVT-BIG significantly improved UPDRS III scores at 4 weeks and UPDRS II scores in the “off” state at 12 weeks, with no ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…In previously published studies, LSVT BIG has been suggested to improve gait speed, UPDRS motor scores, TUG performance, endurance, bed mobility, and other functional measures, potentially more so than other exercise programs such as Nordic walking, home exercise programs, and general treadmill training 1 , 2 , 3 , 10 , 37 ) . However, little research has been conducted on the impact of LSVT BIG on the ability to dual task.…”
Section: Discussionmentioning
confidence: 99%
“…In previously published studies, LSVT BIG has been suggested to improve gait speed, UPDRS motor scores, TUG performance, endurance, bed mobility, and other functional measures, potentially more so than other exercise programs such as Nordic walking, home exercise programs, and general treadmill training 1 , 2 , 3 , 10 , 37 ) . However, little research has been conducted on the impact of LSVT BIG on the ability to dual task.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used the Mini-BESTest to evaluate balance. In contrast to TUG and FRT used in most previous studies assessing the effect of LSVT-BIG [17,18,20,21], this test measures several aspects of dynamic balance. Moreover, as compared to the BBA, the Mini-BESTest total score has no ceiling effect for mild PD [26,38], it is more effective in discriminating between those with and without postural response deficits [38] and predicts the risk of falls slightly better [9,39].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a case-report with three participants found improvements in both balance and gait as per Functional Reach Test (FRT), Functional Gait Assessment (FGA) and TUG [21]. In contrast, another small study including 8 participants did not see significant changes in gait speed and TUG [20]. Recently, a study using a more comprehensive measurement of balance (the Berg Balance Assessment (BBA)), in addition to measurements of gait (gait speed and FGA), reported that eight of the nine participants with mild symptoms had improved their performance in at least one of these measurements after LSVT-BIG intervention [22].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Zwei kontrollierte Interventionen und einige Fallstudien belegen die Wirksamkeit von LSVT-BIG bei Parkinson (11,(19)(20)(21)(22)(23)…”
Section: Studien Zu Lsvt-bigunclassified